Study of the bioaccumulation of some heavy metal elements (Zn, Ni, Co) in the transplanted Lichen Parmelina pastillifera (Harm.) Hale in different areas of Lattakia. - علي , محمود; خليل , كامل; حسن, لبنى (Latakia University Journal -Biological Sciences Series, 2021)
This study aimed to estimate the concentration of heavy metals: zinc (Zn), nickel (Ni) and cobalt (Co) in the thallus of Parmelina pastillifera (Harm.) Hale taken from the Cedar - fir protected area in the unpolluted Slenfe area (control area: STC) on 1/6/2019 and transferred to Four locations in Lattakia (rural and urban), differing according to traffic density and industrial activities, These are: ST1 a rural area (Ain al-Bayda village), ST2 a medium-traffic area (Ghassan Harfouche Street), ST3 a heavy-traffic area (Al-Thawra Highway Roundabout), and ST4 an industrial area for the production of plastic pipes and recycling (Shabatlya village). The concentration of the elements was determined by using the atomic absorption spectrophotometer after placing the lichen in the four sites for a period of 2, 4, and 6 months of exposure. The results showed an increase in Zn accumulation after a period of 2 months, then it began to decrease with time, and the highest values were in the fourth site (147.54) ppm, As for nickel, an increase in the accumulation of the element was observed with the increase in the exposure period and the highest values were in the fourth site (48.51) ppm. The cobalt element recorded an increase in accumulation and then a decrease with time in most of the studied sites. It was noticed by calculating the average values of the Exposure- to -Control (EC ratio) at the end of the study that the area has low zinc pollution (1.48), high for nickel (3.2) and severe for cobalt (5.11). As a result, we can suggest transplanted lichen Parmelina pastillifera as an active bioaccumulator for assessing the degree of heavy metal pollution.